Ungdoms engstelse for vold omfang, årsaker og konsekvenser - Gautun, Heidi (Nordisk Tidsskrift for Kriminalvidenskab, 1997)
One out of two youths, aged 15-24 years, reported in 1995 that they had been anxious of being exposed to violence when they went downtown in the evenings in the capital Oslo. Twenty percent said they had been anxious to experience violence when they visited friends in the neighbourhood or on their way to school. Youths living in rural districts feel more safe. The majority of respondents without a recent experience of violence reported that they were anxious due to the frequent media-coverage of violence-episodes. A minority have been exposed to violence. About 1/3 reports that they are anxious because of their own experience with violence. Anxiety of violence is common in Oslo, and a majority of the youths use strategies to avoid violence.